Determination of Radiation Dose Rate and Dose Analysis of Radiation Workers in Radiology Installation at Pariaman Hospital - Ramacos Fardela; Susi Andriati; Feriska Handayani Irka; Almahdi Mousa; Ade Wahyuni (Lambung Mangkurat University Press, 2024)
Diagnostic radiology is the most significant contributor to irradiation in the general population. Unnecessary irradiation of workers, patients, and the public during radiological procedures should be significantly reduced without affecting the medical diagnostic value. This study was conducted to analyze and evaluate the radiation dose rate, radiation protection facilities and radiation worker dose of Radiology Installation of Pariaman Regional Hospital. The method of determining the radiation dose rate at the Radiology Instalansi of Pariaman Hospital uses a PDR 303 gamma surveymeter and the rooms to be measured are CT-Scan rooms, conventional X-rays and mammography. Collecting data on radiation protection facilities, then it will be analyzed based on Nuclear Energy Regulatory Agency Regulation No. 4 of 2020 and radiation worker dose data in 2023 will be analyzed based on Nuclear Energy Regulatory Agency Regulation No. 4 of 2013. The results of the study showed that the radiation dose rate around the CT-Scan room was found to be (0.24-1.61) μSv/hour, the conventional X-ray room with irradiation using the minimum exposure factor obtained a radiation dose rate around the room ranging from (0.013-0.33) μSv/hour and with the maximum exposure factor obtained a dose rate around the room of (0.33-1.08) μSv/hour and the mammography room obtained a radiation dose rate of (0.03-0.40) μSv/hour. The radiology room facilities used by Pariaman Hospital are in accordance with the standards set by Nuclear Energy Regulatory Agency Regulation No. 4 of 2020. And the dose rate received by radiation workers at Pariaman Hospital is below the Dose Limit Value set by Nuclear Energy Regulatory Agency Regulation No. 4 of 2013. Based on the results of this study, it is found that there are several measurement points in the CT-Scan and conventional X-ray rooms that exceed the community dose limit value.